C-104 Special lecture: Rotavirus and Rotavirus Vaccines. (March 2017) - Glass, Roger
Abstract : Rotavirus vaccines have been introduced into the routine immunization programs of more than 80 countries. Their impact has been rapid with the reduction in diarrheal illnesses, hospitalizations, and deaths. With this introduction have been a number of changes in the epidemiology of rotavirus infections that could not have been properly anticipated beforehand including the demonstration of herd or community protection in non-vaccinated children, older children and adults, the changing age distribution of disease, a decrease in seizure related hospitalizations, and what may be a new biannual distribution of disease peaks similar to what was seen for measles before routine vaccination. Unfortunately, these live oral vaccines have proven to be less effective in some low income settings where they are needed most. Research has identified a number of possible explanations—interference from simultaneous OPV administration, high titers of transplacental antibodies, and differences in the microbiome of children in these settings, none of which are easy to change. Consequently, we have embarked on the development of a parenteral inactivated rotavirus vaccine (IRV) with the hope that this product would improve the efficacy of a rotavirus vaccine in all settings while avoiding recurrent concerns about intussusception that has occurred with all these live oral rotavirus vaccines. Immunization of piglets with an IRV has stimulated cross-reacting neutralization antibodies while protecting these animals against virus shedding when challenged with wild type rotavirus strains. Work is ongoing to develop a candidate vaccine suitable for testing in humans.